COMPARATIVE ANALYSIS OF PERFORMANCE CRITERIA IN SOLUTION OF NONUNIFORM MINIMAX PROBLEM BY LIST ALGORITHM - Valery G. Kobak; Mikhail A. Muratov (Advanced Engineering Research)
V.N.Plotnikov - V.J.Zverev list algorithm is examined. Minimax, quadratic and cubic criteria are used. The software for the analysis of criteria efficiency is developed.